Topical treatment of canine pyodermas - KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ), A. F.; SARIDOMICHELAKIS (Μ.Ν. ΣΑΡΙΔΟΜΙΧΕΛΑΚΗΣ), M. N. (Journal of the Hellenic Veterinary Medical Society, 2018)
Topical treatment in canine pyodermas helps to reduce or eliminate the surface bacterial population and to restore the epidermal and follicular integrity. In most superficial and deep pyodermas topical treatment rarely works when used alone; however, its judicious use can make the patient more comfortable and hasten the response to systemic antibiotics. Conversely, in surface pyodermas or pseudopyodermas topicals usually suffice. Among various antimicrobials, the most commonly used include benzoyl peroxide, ethyl lactate, povidone-iodine, triclozan and some antibiotics such as mupirocin, fucidic acid, neomycin and clindamycin. In addition, other topical medication like glucocorticoids, astrigents and dessicating powders are usually applied in dogs with surface pyodermas. Finally, hydrotherapy is very helpful in deep pyoderma cases in the form of wet dressings or baths. The effectiveness of topical treatment depends on the appropriate selection of the active ingredient and its delivery system (formulations), that should accommodate the kind, the distribution and the extension of skin lesions.